A SIYASAH SYAR’IYYAH REVIEW OF THE CONSTITUTIONAL COURT DECISION NUMBER 55/PUU-XVII/2019 ON THE 2019 SIMULTANEOUS GENERAL ELECTIONS - Selsa, Febi Lianda; Maloko, M Thahir; Zakirah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
Simultaneous general elections are electoral systems that hold several elections at the same time. The purpose of this study was to determine the views of siyasa syariyyah on the decision of the Constitutional Court No. 55/PUU-XVII/2019 regarding the 2019 simultaneous elections. This research uses normative, juridical, and syar’i research. The results of this study indicate that the concept of the 2019 simultaneous elections against the Constitutional Court’s decision no. 55/PUU-XII/2019 encourages the strengthening of the presidential system and is more efficient, both in terms of financing and the time of holding simultaneous elections. However, in the community, this is the first simultaneous election that has been held, leaving several problems that still need to be evaluated and reconsidered until the next period. The view of the Syariyyah siyasa regarding simultaneous general elections has existed since time immemorial, although the implementation is not exactly the same today. Elections in Islam are called waqalah and the law is permissible (permissible). Elections have similarities with the bai’at method carried out at the time of the Prophet and Khulafa al-Rashidin. In addition, a more appropriate and efficient way has not been found to replace the election method.